Peningkatan Hasil Belajar Materi Memahami Teknik Melempar Bola Melalui Penerapan Model Kooperatif Tipe Snowball Throwing - Abdul Qowi (Departement of Mathematics Education, 2021)
After a year and a half of online learning due to the Covid-19 pandemic, face-to-face learning is limited to taking into account strict health procedures. Limited face-to-face learning (PTMT) is not necessarily the same as face-to-face learning before the Covid-19 pandemic occurred, because it contains elements that collaborate face-to-face learning with online learning, which in contemporary terms is called hybrid learning. Therefore, the intensification of face-to-face learning activities is a determinant of learning success so that the learning outcomes obtained by students can be maximized. The purpose of this study was to determine whether or not there was an increase in learning outcomes in Understanding Ball Throwing Techniques through the application of the Snowball Throwing Cooperative model in grade 3-A students of SD Negeri Wonokusumo IV/43 Surabaya. This research was conducted at SD Negeri Wonokusumo IV/43, Semampir sub-district, Surabaya City with a two-cycle action research mechanism. Based on data analysis, from this study it can be concluded that there is an increase in learning outcomes in Understanding Ball Throwing Techniques through the application of the Snowball Throwing Cooperative model in grade 3-A students of SD Negeri Wonokusumo IV/43 Surabaya.